2007
DOI: 10.4161/cbt.6.12.5164
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 regulates γ-tubulin binding to centrosomes

Abstract: Centrosomes are the cellular organelles that nucleate microtubules (MTs) via the activity of gamma-tubulin ring complex(s) (gammaTuRC) bound to the pericentriolar material of the centrosomes. BRCA1, the breast and ovarian cancer specific tumor suppressor, inhibits centrosomal MT nucleation via its ubiquitin ligase activity, and one of the known BRCA1 substrates is the key gammaTuRC component, gamma-tubulin. We analyzed the mechanism by which BRCA1 regulates centrosome function using an in vitro reconstitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 20 publications
3
41
0
Order By: Relevance
“…Therefore, the g-tubulin content in the centrosome regulates MT nucleation function (14). Previous studies found that ubiquitination of g-tubulin by BRCA1/BARD1 during the S and G 2 phases (13,14) has a significant role in regulating MT nucleation, which further prevents aberrant reduplication of the centrosomes (15). This could imply that g-tubulin ubiquitination directly inhibits centrosome microtubule nucleation function.…”
Section: G-tubulin Is a Substrate For The Deubiquitinating Enzyme Bap1mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the g-tubulin content in the centrosome regulates MT nucleation function (14). Previous studies found that ubiquitination of g-tubulin by BRCA1/BARD1 during the S and G 2 phases (13,14) has a significant role in regulating MT nucleation, which further prevents aberrant reduplication of the centrosomes (15). This could imply that g-tubulin ubiquitination directly inhibits centrosome microtubule nucleation function.…”
Section: G-tubulin Is a Substrate For The Deubiquitinating Enzyme Bap1mentioning
confidence: 99%
“…Furthermore, during mitosis there is a sudden increase of the g-tubulin content in the centrosome (28), and mitotic centrosomes exhibit enhanced MT nucleation capacity (29). Therefore, the g-tubulin content in the centrosome regulates MT nucleation function (14). Previous studies found that ubiquitination of g-tubulin by BRCA1/BARD1 during the S and G 2 phases (13,14) has a significant role in regulating MT nucleation, which further prevents aberrant reduplication of the centrosomes (15).…”
Section: G-tubulin Is a Substrate For The Deubiquitinating Enzyme Bap1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its major role in DNA repair, BRCA1 also regulates centrosome duplication. BRCA1 binds to centrosomes and mitotic spindle poles (Hsu and White, 1998); its structural partners at the centrosome include the microtubule-nucleating protein -tubulin and proteins that control mitotic spindle assembly (Hsu and White, 1998;Joukov et al, 2006;Sankaran et al, 2007). BRCA1 ubiquitinates -tubulin and prevents its over-recruitment to the centrosome (Sankaran et al, 2007;Starita et al, 2004).…”
Section: Centrosome-interacting Tumor Suppressors: P53 and Brca1mentioning
confidence: 99%
“…BRCA1 binds to centrosomes and mitotic spindle poles (Hsu and White, 1998); its structural partners at the centrosome include the microtubule-nucleating protein -tubulin and proteins that control mitotic spindle assembly (Hsu and White, 1998;Joukov et al, 2006;Sankaran et al, 2007). BRCA1 ubiquitinates -tubulin and prevents its over-recruitment to the centrosome (Sankaran et al, 2007;Starita et al, 2004). In its absence, cells develop supernumerary centrosomes that show an increased microtubule-nucleating capacity (Starita et al, 2004;Xu et al, 1999).…”
Section: Centrosome-interacting Tumor Suppressors: P53 and Brca1mentioning
confidence: 99%